KEPUTUSAN PEMBELIAN DITINJAU DARI GAYA HIDUP, KELOMPOK REFERENSI, INOVASI PRODUK (STUDI PADA PENJUAL ONLINE SEPEDA MINIONS MODERN SURAKARTA) - Saptono Setya Prabowo; Ida Aryati; Istiqomah Istiqomah (JURNAL ILMIAH EDUNOMIKA, 2020)
The purpose of this study is to find out whether there is a significant influence between Lifestyle variables, reference groups and product innovations on Purchasing Decisions. In addition, it is also to find out whether there is a significant simultaneous effect and which variable is the most dominant in influencing Purchase Decisions on Surakarta Online Minions Bike Modern Seller. The method used is quantitative descriptive method. The population in this study amounted to more than 100 consumers, and the number of samples used was 100, where the sampling technique used purposive sampling. The data used are primary data and secondary data with data collection techniques: observation, questionnaire, interview. Data analysis techniques in this study used multiple linear tests. The results of the study can be concluded that: The results of the study can be concluded that: 1) There is an influence of Lifestyle, reference groups, and product innovations simultaneously influence the Purchasing Decision on the Online Seller of the Modern Minions Bicycle in Surakarta, 2) There is the influence of Lifestyle on the Purchasing Decision of the Online Seller Surakarta Modern Minions Bicycles 3) There is the influence of reference groups on Purchasing Decisions on Online Sellers Surakarta Modern Minions Bicycles, 4) There is an influence of product innovation on Purchasing Decisions on Surakarta Modern Minions Bicycles Online Sellers Keywords: Purchasing Decisions, Lifestyle, reference groups and product innovation